2017
DOI: 10.15578/iaj.12.2.2017.67-75
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF VIRAL PROTEIN, VP-15, OF WHITESPOT SYNDROME VIRUS ISOLATED FROM INFECTED TIGER SHRIMP Penaeus monodon (Fabricius, 1798)

Abstract: White spot syndrome virus (WSSV) has caused mass mortality on tiger shrimp (Penaeus monodon) culture and adversely affects prawn industry worldwide including Indonesia. It is well known that the protein structure of WSSV plays an important role in the virus infection and morphogenesis process. A viral protein structure called VP-15 is located in the nucleocapsid of virion virus. The protein structure involves in the life cycle of WSSV in host cells. A gene encoding VP-15 could be involved in constructing the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Aplikasi vaksin dsRNA khususnya gen virulensi penkode viral protein (VP) dari WSSV pada udang windu masih sangat terbatas. Sebagai langkah awal, telah dilakukan karakterisasi gen penyandi VP-15 dan VP-24 dari WSSV dan aplikasi dsRNA yang diproduksi secara in vitro (Tenriulo et al, 2016;Parenrengi et al, 2017;Parenrengi et al, 2018;Mulyaningrum et al, 2018). Produksi dsRNA secara in vitro menggunakan kit masih terkendala dalam hal biaya produksi yang tinggi dan rekombinan dsRNA.…”
Section: Pendahuluanunclassified
“…Aplikasi vaksin dsRNA khususnya gen virulensi penkode viral protein (VP) dari WSSV pada udang windu masih sangat terbatas. Sebagai langkah awal, telah dilakukan karakterisasi gen penyandi VP-15 dan VP-24 dari WSSV dan aplikasi dsRNA yang diproduksi secara in vitro (Tenriulo et al, 2016;Parenrengi et al, 2017;Parenrengi et al, 2018;Mulyaningrum et al, 2018). Produksi dsRNA secara in vitro menggunakan kit masih terkendala dalam hal biaya produksi yang tinggi dan rekombinan dsRNA.…”
Section: Pendahuluanunclassified
“…Ekstraksi genomik DNA dilakukan dengan metode CTAB yang telah dikembangkan pada udang windu (Parenrengi et al, 2017).…”
Section: Bahan Dan Metodeunclassified
“…Hasil pengurutan sekuens nukleotida dengan menggunakan target pembacaan open reading frame (ORF) sekitar 243 bp yang dimulai dengan adanya kodon awal "ATG" (start codon) dan diakhiri dengan kodon akhir " TA A" (stop codon) (Gambar 3). Karakterisasi gen VP-15 isolat dari Takalar, Indonesia yang mewabah pada tahun 2012, 2013, dan 2014 telah dilakukan oleh Parenrengi et al (2017) Hidayani et al (2016) juga melaporkan bahwa isolat WSSV (VP-19) yang menginfeksi udang vaname di Indonesia memiliki kerabatan yang dekat dengan isolat WSSV dari Meksiko. Kemiripan sekuens gen VP-19 WSSV isolat Situbondo dengan isolat Indonesia lainnya maupun dari negara-negara lain mencapai 98% (Alim et al, 2011).…”
Section: Analisis Sekuens Nukleoitida Gen Sisipan Vp-15unclassified
“…A gene encoding VP15 was isolated from tiger shrimp infected by W SSV and cloned into the L4440 vector containing the T7 promoter. The pT7-VP15 gene construct was transformed to bacteria Escherichia coli DH5 (Parenrengi et al, 2017). Bacteria were grown on liquid LB media in a 15 mL test tube and then incubated overnight at 37  C at a 120 rpm.…”
Section: Preparing Of Dsrna Vaccinementioning
confidence: 99%
“…The identification and characterization of the VP15 have been reported (Van Hulten et al, 2002;W itteveldt et al, 2005;Xing and Shi, 2011) and its applications have been demonstrated the potential way to use for protecting the viral shrimp diseases (Boonyakida et al, 2020). A gene encoding VP15 isolated from WSSV infected tiger shrimp Application of dsRNA VP15-WSSV by Oral Vaccination to Increase Survival Rate and Response Immunes of Tiger Shrimp... in Indonesia has been identified and characterized by Parenrengi et al (2017). The successful production by invitro using MEGAscript RNAi kit and in-vivo (Mulyaningrum et al, 2018;Parenrengi et al, 2018) has been proven led to apply in aquaculture for preventing the WSD.…”
Section: Introductionmentioning
confidence: 99%